The Effect Of Investment, Economic Growth, Inflation, Drinking Wages And HDI On Open Unemployment In The Kalimantan Regional - Sunaryo N Tuah; Benius Benius; Natalia Br Ginting (Fakultas Ekonomi dan Bisnis Universitas Palangka Raya, 2022)
This study aims to provide an empirical explanation of the effect of Investment, Economic Growth, Inflation, Minimum Wage and HDI on Open Unemployment in Kalimantan Region. The research method used is panel data regression analysis method using Fixed Effect Model (FEM). The type of data used is secondary data. Secondary data obtained from the Central Statistics Agency (BPS) Kalimantan Region. The data that has been collected is then analyzed with panel data regression using the Fixed Effect Model where this model uses the Chow Test and Hausman Test to see the Effect of Investment, Economic Growth, Inflation, Minimum Wage and HDI on Open Unemployment in Kalimantan Region using Stata 16.0 software. The results of the analysis in this study indicate that Investment, Economic Growth, Inflation, Minimum Wage and HDI have a significant effect on Open Unemployment in Kalimantan